Carbon-coated current collector, preparation method thereof, pole piece and battery

CN120784378BActive Publication Date: 2026-10-30JIANGYIN NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510860027.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2026-10-30
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

然而,在涂碳集流体制作过程中会出现漏涂、灰点等缺陷,这些缺陷会造成样品表面涂层厚度不均匀,影响涂层的外观和性能

Benefits of technology

[0024]本发明通过在涂碳浆料中添加阴离子型表面活性剂和苷类化合物,显著降低涂碳浆料的表面张力,提高涂碳浆料的润湿性,确保涂碳浆料在铝箔表面的流平。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120784378B_ABST
    Figure CN120784378B_ABST
Patent Text Reader

Abstract

The application discloses a kind of carbon-coated current collector and preparation method thereof, pole piece and battery, the application is by adding anionic surfactant and glycoside compound in carbon-coated slurry, significantly reduce the surface tension of carbon-coated slurry, improve the wettability of carbon-coated slurry, ensure that carbon-coated slurry is on the surface of aluminum foil Leveling, reduce the surface defect of carbon-coated current collector carbon-coated layer, improve product quality.Anionic surfactant and glycoside compound of the application are used in compound, so that the wetting and dispersion stability of anionic surfactant is optimized and improved, so that the performance of carbon-coated slurry system is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, specifically to a carbon-coated current collector and its preparation method, an electrode, and a battery. Background Technology

[0002] Lithium-ion batteries (LIBs) have been widely used in various fields such as consumer electronics, transportation, power tools, and energy storage. The aluminum foil current collector in lithium-ion batteries is a process of combining aluminum foil with other materials such as paper, plastic film, and coatings to form a composite material. This technology can endow aluminum foil with new properties and functions to meet the needs of different industries.

[0003] To improve the performance of lithium batteries, the lithium battery industry employs a carbon-coated current collector strategy to increase the rate of operation and overall performance. However, defects such as incomplete coating and gray spots can occur during the manufacturing process of carbon-coated current collectors. These defects result in uneven coating thickness on the sample surface, affecting the appearance and performance of the coating. This can also lead to a reduction in the safety performance of lithium batteries, as coating defects weaken the protective effect of the coating, making it more susceptible to damage in high-temperature, high-pressure, and corrosive environments. Therefore, it is essential to minimize surface defects during the manufacturing process of carbon-coated current collectors to improve product quality. Summary of the Invention

[0004] The purpose of this invention is to provide a carbon-coated current collector and its preparation method, as well as an electrode and a battery, thereby reducing surface defects in the carbon coating layer of the carbon-coated current collector and improving product quality.

[0005] The first aspect of this application provides a carbon-coated current collector, wherein the carbon coating layer of the carbon-coated current collector contains anionic surfactants and glycoside compounds.

[0006] The anionic surfactant is sodium dodecylbenzenesulfonate, and the glycoside compound is a saponin.

[0007] The second aspect of this application provides a method for preparing a carbon-coated current collector, wherein an anionic surfactant and a glycoside compound are added and mixed evenly during the preparation of the carbon-coated slurry to obtain a mixed slurry; the mixed slurry is then coated onto a current collector to obtain a carbon-coated current collector.

[0008] To optimize the above technical solution, the specific measures also include:

[0009] The total amount of the anionic surfactant and glycoside compound added is in a mass ratio of 1:7 to 11 to the conductive agent in the carbon coating slurry; the mass ratio of the anionic surfactant and glycoside compound is 1:2 to 3.

[0010] The carbon coating slurry also includes a binder, a conductive agent, and a pH adjuster; the anionic surfactant and glycoside compound are added after the binder and conductive agent are added, and the pH adjuster is used to adjust the slurry to a weakly acidic state before adding them. When adding them, the anionic surfactant is added first, and after mixing, the glycoside compound is added.

[0011] The preparation of the carbon coating slurry includes the following steps:

[0012] S1: Dilute the adhesive with water;

[0013] S2: Add the conductive agent to the diluted adhesive in several batches, ensuring that the conductive agent is evenly dispersed after each addition;

[0014] S3: Add water to reduce the slurry concentration and ensure uniform dispersion;

[0015] S4: Add pH adjuster to adjust pH to 5-6.5;

[0016] S5: Add an anionic surfactant and disperse evenly;

[0017] S6: Add glycoside compounds and disperse evenly;

[0018] S7: Perform thorough homogenization to obtain a mixed slurry.

[0019] Further, the uniform dispersion mentioned in steps S2 and S3 is achieved by high-speed dispersion at a rotation speed of 2000-2600 rpm / min for 15-40 min; the uniform dispersion mentioned in steps S5 and S6 is achieved by low-speed dispersion at a rotation speed of 10-15 rpm / min for 30-50 min; and the thorough homogenization mentioned in step S7 is achieved by homogenizing 2-3 times in a homogenizer at a pressure of 200-400 bar.

[0020] Furthermore, the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent is carbon powder, the second conductive agent is graphite powder, and the mass ratio of the first conductive agent to the second conductive agent is 5-7:3-6; the pH adjuster is sodium hydroxide solution, lithium hydroxide solution, or sodium bicarbonate solution.

[0021] A third aspect of this application provides a battery electrode comprising a carbon-coated current collector prepared by the above method.

[0022] A fourth aspect of this application provides a battery comprising the aforementioned battery electrodes.

[0023] Compared with the prior art, the beneficial effects of the present invention are:

[0024] This invention significantly reduces the surface tension of the carbon coating paste and improves its wettability by adding anionic surfactants and glycoside compounds, thus ensuring the leveling of the carbon coating paste on the aluminum foil surface.

[0025] The combined use of anionic surfactants and glycosides in this application optimizes and improves the wetting and dispersion stability of anionic surfactants, resulting in better performance of the carbon coating slurry system. When anionic surfactants are added alone, their stability to the carbon coating slurry decreases. However, the rapid surface tension reduction ability of glycosides combined with the persistence and stability of anionic surfactants forms a more effective surfactant system. The combination of these two surfactants can form a denser molecular layer, further reducing surface tension and improving wetting effect. Attached Figure Description

[0026] Figure 1 : Ordinary carbon-coated current collector (Comparative Example 1).

[0027] Figure 2 The carbon-coated current collector of the present invention (Example 1). Detailed Implementation

[0028] The present invention will be further described in detail below through specific embodiments, but it should not be construed as limiting the scope of the subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.

[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the reagents, methods and equipment used are conventional reagents, methods and equipment in this technical field.

[0030] For the sake of brevity, this article only discloses some numerical values ​​and the range of options. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range. Similarly, any upper limit can be combined with any other upper limit to form an unspecified range; the options in the range of options can also be combined arbitrarily.

[0031] Unless otherwise stated, the terms used in this application have their common meanings as commonly understood by those skilled in the art. Unless otherwise stated, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.

[0032] The present invention provides a carbon-coated current collector, wherein the carbon coating layer of the carbon-coated current collector contains anionic surfactants and glycoside compounds.

[0033] In the preferred embodiment of this application, the anionic surfactant is sodium dodecylbenzenesulfonate, and the glycoside compound is a saponin.

[0034] Among other alternatives, anionic surfactants such as sodium dioctyl succinate, sodium dodecyl sulfate, and sodium fatty alcohol polyoxyethylene ether sulfate can also be used.

[0035] In other alternatives, glycosides such as flavonoid glycosides, coumarin glycosides, and phenolic glycosides can also be used.

[0036] Anionic surfactants can significantly reduce the surface tension of liquids, making it easier for carbon coating slurries to wet solid surfaces and improve coating uniformity. Anionic surfactants also have good dispersing properties, which can prevent the agglomeration of solid particles in carbon coating slurries, ensuring that particles are uniformly dispersed in the slurry, thereby improving the stability of the slurry and the quality of the coating.

[0037] Sodium dodecylbenzenesulfonate (SDBS) is preferred. SDBS has strong surface activity and dissociates in aqueous solution into dodecylbenzenesulfonate ions (hydrophobic tail) and sodium ions (hydrophilic head). The hydrophobic tail inserts into the surface of the carbon paste, forming an ordered molecular layer and reducing surface tension. The negatively charged sulfonate ions of SDBS attract positive ions to form an electric double layer, further reducing the surface tension of the carbon-coated paste. By inserting its hydrophobic tail into the carbon paste surface, it lowers the interfacial energy at the liquid-solid interface. Therefore, a small amount of SDBS can significantly improve the wettability and dispersibility of the carbon-coated paste. SDBS is also environmentally friendly and economical. Under appropriate usage conditions, it exhibits good biodegradability, reducing environmental impact. It is a relatively inexpensive surfactant that can lower production costs.

[0038] Glycoside compounds exhibit good wettability and strong surface activity. Our research has verified that glycoside compounds, when applied to carbon coating slurries, can effectively adsorb surfactants, form an electric double layer, and reduce interfacial energy.

[0039] Surfactant adsorption: Hydrophilic groups (such as glycosyl groups) in glycosides tend to bind with water molecules, while hydrophobic groups (such as steroid skeletons) tend to move away from water molecules. When glycosides are added to carbon-coated slurry, their hydrophobic tails will preferentially adsorb onto the surface of the carbon slurry to form a monolayer, reducing the surface tension of the liquid.

[0040] Forming an electric double layer and reducing interfacial energy: The hydrophilic groups of glycosides carry negative charges, which can attract surrounding positive ions (such as Na+), forming an electric double layer structure on the surface of the carbon-coated paste. The presence of the electric double layer further reduces the surface tension.

[0041] Saponins are preferred because they are naturally derived from plants, have good environmental friendliness and biodegradability; they have strong surface activity, which can significantly reduce the surface tension of liquids, improve the wettability of carbon coating slurry to the substrate, and ensure a more uniform coating; they have good dispersing properties, which can effectively disperse solid particles in carbon coating slurry, prevent particle agglomeration, and enhance the stability and uniformity of the coating; and they are milder than some chemically synthesized surfactants, generally being gentler on the skin and in the environment, making them suitable for use in applications requiring low irritation and environmental friendliness.

[0042] Examples of saponin extraction and synthesis are as follows:

[0043] 1. Sample preparation: Take 10 portions of pear peel needed for the experiment and dry them in a constant temperature drying oven for more than 100 hours to ensure that the samples are clean and free of moisture; then take out the completely dried pear slices and grind them into pear peel powder using a mortar and pestle.

[0044] 2. Degreasing extraction: Mix the dried and processed pear slice powder with ethanol, and extract the mixture by shaking at a frequency of 3000Hz in a 50℃ constant temperature water bath. This step requires 4-6 small-scale experiments.

[0045] 3. Filter the extract through a 200-mesh filter to remove solid residue.

[0046] 4. Concentrate the filtered solution on a rotary evaporator to obtain a concentrated solution containing saponins.

[0047] 5. Column purification: The treated concentrate is purified by passing it through a silica gel column to remove impurities.

[0048] 6. Elution and collection: Elute the saponins with appropriate pure water and collect the eluent.

[0049] 7. Concentration and crystallization: The collected eluent is concentrated in a rotary evaporator to obtain a concentrated solution containing saponins, which is then cooled or cryogenically precipitated to obtain saponin crystals.

[0050] 8. The obtained saponin crystals were dried in a vacuum drying oven at 50°C for 20 hours to obtain pure saponin powder.

[0051] The combination of anionic surfactants and glycosides in this application can produce a synergistic effect, which can optimize and improve the wetting and dispersion stability of anionic surfactants, and make the performance of carbon coating slurry system better.

[0052] When anionic surfactants are added alone, their stability is reduced. However, the ability of glycosides to rapidly reduce surface tension, combined with the persistence and stability of anionic surfactants, forms a more effective surfactant system. The combination of these two surfactants can form a denser molecular layer, further reducing surface tension and improving wetting effect.

[0053] The present invention also provides a method for preparing a carbon-coated current collector, wherein anionic surfactant and glycoside compound are added and mixed evenly during the preparation of carbon-coated slurry to obtain a mixed slurry; the mixed slurry is coated on a current collector to obtain a carbon-coated current collector.

[0054] In some embodiments, the total amount of anionic surfactants and glycosides added is in a mass ratio of 1:7 to 11 to the conductive agent in the carbon coating slurry; the mass ratio of anionic surfactants and glycosides is 1:2 to 3.

[0055] The carbon coating slurry also includes binders, conductive agents, and pH adjusters. The anionic surfactants and glycosides are added after the binders and conductive agents are added, and the pH adjuster is used to adjust the slurry to a weakly acidic state before adding them. When adding them, the anionic surfactants are added first, and after mixing, the glycosides are added.

[0056] In some preferred embodiments, the binder has a solid content of 15-30% and a viscosity of 800-3500 mPa·s.

[0057] In some embodiments, the preparation of the carbon coating slurry includes the following steps:

[0058] S1: Dilute the adhesive with water;

[0059] S2: Add the conductive agent to the diluted adhesive in several batches, ensuring that the conductive agent is evenly dispersed after each addition;

[0060] S3: Add water to reduce the slurry concentration and ensure uniform dispersion;

[0061] S4: Add pH adjuster to adjust pH to 5-6.5;

[0062] S5: Add an anionic surfactant and disperse evenly;

[0063] S6: Add glycoside compounds and disperse evenly;

[0064] S7: Perform thorough homogenization to obtain a mixed slurry.

[0065] The uniform dispersion in steps S2 and S3 refers to high-speed dispersion at a rotation speed of 2000-2600 rpm / min for 15-40 min; the uniform dispersion in steps S5 and S6 refers to low-speed dispersion at a rotation speed of 10-15 rpm / min for 30-50 min; the thorough homogenization in step S7 refers to homogenization in a homogenizer at a pressure of 200-400 bar 2-3 times.

[0066] In some embodiments, the conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent is carbon powder and the second conductive agent is graphite powder, and the mass ratio of the first conductive agent to the second conductive agent is 5-7:3-6; the pH adjuster is a sodium hydroxide solution, a lithium hydroxide solution, or a sodium bicarbonate solution.

[0067] In some preferred embodiments, the binder has a solid content of 15-25%, and the mass ratio of binder to conductive agent is 20-25:5-6.

[0068] The present invention also provides a battery electrode comprising the above-described carbon-coated current collector.

[0069] The present invention also provides a battery comprising the battery electrode sheets described above.

[0070] The technical solution of the present invention will be further described in detail below with reference to specific embodiments:

[0071] Example 1

[0072] A carbon-coated current collector, the preparation of which includes the following steps:

[0073] (1) Mix 60L of deionized water with 20kg of polyacrylic acid (PAA) with a solid content of 20% to reduce the solid content of the adhesive;

[0074] (2) Add 1.7 kg of half conductive carbon powder and 1.3 kg of half conductive graphite powder, and disperse them at high speed of 2000-2600 rpm / min for 30 min in a 200L double star stirring tank;

[0075] (3) Add 1.7 kg of the other half of the conductive agent carbon powder and 1.3 kg of the other half of the conductive agent graphite powder, and disperse them at high speed of 2000-2600 rpm / min for 60 min in a 200L double star stirring tank.

[0076] (4) Add 30L of deionized water to reduce the slurry concentration, and disperse at high speed for 30 minutes at 2000-2600rpm / min in a 200L double star mixing tank;

[0077] (5) Add 10 kg of 0.1 mM sodium hydroxide solution as a pH adjuster to adjust the pH to 6;

[0078] (6) Add 200g of anionic surfactant sodium dodecylbenzenesulfonate and stir at a low speed of 10-15rpm / min for 30-45min in a 200L double star stirring tank;

[0079] (7) Add 550g of glycoside compound saponin, stir at low speed of 10-15rpm / min for 30-45min in a 200L double star stirring tank, and then discharge the material;

[0080] (8) Homogenize the slurry twice in a homogenizer at a pressure of 300 bar to obtain carbon-coated slurry;

[0081] (9) The carbon-coated slurry is evenly coated onto the current collector to obtain a carbon-coated current collector sample with high adhesion.

[0082] Sodium dodecylbenzenesulfonate in this embodiment was purchased from Sinopharm Group, model AR (Shanghai Test), ≥88.0%.

[0083] In this embodiment, the total mass ratio of sodium dodecylbenzenesulfonate and saponin to the mass ratio of the conductive agent is 1:8.

[0084] The carbon-coated current collector has a single-sided carbon coating thickness of 0.5 μm; the surface tension of the slurry and the number of defects on the carbon-coated aluminum foil per square decimeter will be tested on the prepared sample.

[0085] Example 2

[0086] In this embodiment, 80g of sodium dodecylbenzenesulfonate, an anionic surfactant, and 220g of saponin, a glycoside compound, were added; the total mass ratio of sodium dodecylbenzenesulfonate and saponin to the mass ratio of the conductive agent was 1:20, and other aspects were the same as in Example 1.

[0087] Example 3

[0088] In this embodiment, 100g of anionic surfactant sodium dodecylbenzenesulfonate and 300g of glycoside compound saponin were added; the total mass ratio of sodium dodecylbenzenesulfonate and saponin to the conductive agent was 1:15, and other aspects were the same as in Example 1.

[0089] Example 4

[0090] In this embodiment, 160g of sodium dodecylbenzenesulfonate, an anionic surfactant, and 440g of saponin, a glycoside compound, were added; the total mass ratio of sodium dodecylbenzenesulfonate and saponin to the mass ratio of the conductive agent was 1:10, and other aspects were the same as in Example 1.

[0091] Example 5

[0092] In this embodiment, 320g of anionic surfactant sodium dodecylbenzenesulfonate and 880g of glycoside compound saponin were added; the total mass ratio of sodium dodecylbenzenesulfonate and saponin to the mass ratio of conductive agent was 1:5, and other aspects were the same as in Example 1.

[0093] Example 6

[0094] In this embodiment, 375g of anionic surfactant sodium dodecylbenzenesulfonate and 375g of glycoside compound saponin were added, and the rest was the same as in Example 1.

[0095] Example 7

[0096] In this embodiment, 150g of sodium dodecylbenzenesulfonate, an anionic surfactant, and 600g of saponin, a glycoside compound, were added. The rest was the same as in Example 1.

[0097] Example 8

[0098] In this embodiment, the anionic surfactant is sodium dioctyl succinate, the glycoside compound is flavonoid glycoside, and the rest is the same as in Example 1.

[0099] Example 9

[0100] In this embodiment, the anionic surfactant is sodium fatty alcohol polyoxyethylene ether sulfate, the glycoside compound is coumarin glycoside, and the rest is the same as in Example 1.

[0101] Comparative Example 1

[0102] Carbon-coated current collector samples were prepared using only an equal amount of the common wetting agent isopropanol without adding anionic surfactants or glycosides.

[0103] Comparative Example 2

[0104] Step (5) of adjusting the pH by adding a pH adjuster was not included; otherwise, it was the same as in Example 1.

[0105] Comparative Example 3

[0106] Only sodium dodecylbenzenesulfonate was added in the same amount as in Example 1, and no saponins were added. Everything else was the same as in Example 1.

[0107] The results of the experiments conducted on each embodiment and comparative example are shown in Table 1:

[0108] Table 1 Comparison of test results between each embodiment and the comparative example.

[0109]

[0110] A comparison of Examples 1-5 shows that anionic surfactants and glycosides in the carbon coating slurry reduce the surface tension of the slurry, thus reducing the number of surface defects on the carbon current collector. This effect becomes more pronounced as the mass ratio of anionic surfactants and glycosides increases. However, excessive amounts of anionic surfactants and glycosides (Example 5) can lead to increased slurry viscosity, altered slurry properties, deteriorated rheological properties, uneven coating, and increased defects. The preferred mass ratio of the total amount of anionic surfactants and glycosides added to the conductive agent in the carbon coating slurry is 1:7-11.

[0111] The comparison of Examples 1, 6, and 7 shows that the ratio of anionic surfactant to glycoside has a significant impact on the synergistic effect of the two. When the ratio of anionic surfactant to glycoside is less than 1:2, such as in Example 6 (1:1), the wettability of the slurry is insufficient, and its performance is inferior to that of Example 1. When the ratio is greater than 1:3, such as in Example 7 (1:4), it will cause the slurry to coagulate, and its performance is also inferior to that of Example 1.

[0112] The comparison of Examples 1, 8, and 9 shows that other anionic surfactants and glycosides can also achieve similar effects, but the effect is not as good as the combination of sodium dodecylbenzenesulfonate and saponins.

[0113] The comparison between Example 1 and Comparative Example 1 shows that when using ordinary wetting agents, there is no synergistic effect of anionic surfactants and glycosides. Therefore, the addition of anionic surfactants and glycosides will greatly increase the wettability of the slurry, and its effect is far superior to that of conventional alcohol wetting agents.

[0114] The comparison between Example 1 and Comparative Example 2 shows that if the pH is not adjusted to weakly acidic before adding anionic surfactants and glycosides during preparation, the added anionic surfactants and glycosides will deform and become ineffective. Therefore, it is necessary to adjust the pH of the slurry to ensure the properties of the materials in the slurry.

[0115] The comparison between Example 1 and Comparative Example 3 shows that if only anionic surfactants are added during preparation without the addition of glycosides, the wetting stability of the slurry will be poor, and there is a risk of increased surface tension of the slurry. Therefore, the wetting of the slurry requires the synergistic effect between anionic surfactants and glycosides to ensure the stability and quality of the slurry.

[0116] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent substitutions, and improvements made by those skilled in the art to the above embodiments without departing from the scope of the technical solution of the present invention, based on the technical essence of the present invention, shall still fall within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a carbon-coated current collector, characterized in that: Anionic surfactants and glycoside compounds are added and mixed evenly during the preparation of carbon-coated slurry to obtain a mixed slurry; the mixed slurry is then coated onto a current collector to obtain a carbon-coated current collector. The anionic surfactant is sodium dodecylbenzenesulfonate, and the glycoside compound is a saponin; The total amount of the anionic surfactant and glycoside compound added is in a mass ratio of 1:7~11 to the conductive agent in the carbon coating slurry; the mass ratio of the anionic surfactant and glycoside compound is 1:2~3. The preparation of the carbon coating slurry includes the following steps: S1: Dilute the adhesive with water; S2: Add the conductive agent to the diluted adhesive in several batches, ensuring that the conductive agent is evenly dispersed after each addition; S3: Add water to reduce the slurry concentration and ensure uniform dispersion; S4: Add pH adjuster to adjust pH to 5-6.5; S5: Add an anionic surfactant and disperse evenly; S6: Add glycoside compounds and disperse evenly; S7: Perform thorough homogenization to obtain a mixed slurry; The conductive agent includes a first conductive agent and a second conductive agent, wherein the first conductive agent is carbon powder and the second conductive agent is graphite powder, and the mass ratio of the first conductive agent to the second conductive agent is 5~7:3~6; the pH adjuster is sodium hydroxide solution, lithium hydroxide solution or sodium bicarbonate solution.

2. The method for preparing the carbon-coated current collector according to claim 1, characterized in that: The carbon coating slurry also includes a binder, a conductive agent, and a pH adjuster; the anionic surfactant and glycoside compound are added after the binder and conductive agent are added, and the pH adjuster is used to adjust the slurry to a weakly acidic state before adding them. When adding them, the anionic surfactant is added first, and after mixing, the glycoside compound is added.

3. The method for preparing the carbon-coated current collector according to claim 1, characterized in that: The uniform dispersion in steps S2 and S3 refers to high-speed dispersion at a rotation speed of 2000~2600 rpm / min for 15~40 min; the uniform dispersion in steps S5 and S6 refers to low-speed dispersion at a rotation speed of 10~15 rpm / min for 30~50 min; the thorough homogenization in step S7 refers to homogenization in a homogenizer at a pressure of 200~400 bar 2~3 times.

4. A carbon-coated current collector prepared by the method according to any one of claims 1 to 3, characterized in that: The carbon coating layer of the carbon-coated current collector contains anionic surfactants and glycoside compounds.

5. A battery electrode, characterized in that: The carbon-coated current collector includes the one described in claim 4.

6. A battery, characterized in that: It includes the battery electrode as described in claim 5.

Citation Information

Patent Citations

  • Carbon-coated current collector and preparation method and application thereof

    CN116581302A

  • Method for improving cycling stability of battery, carbon-coated current collector and battery positive plate

    CN118919735A